HUBUNGAN USIA, JARAK KEHAMILAN DAN ANEMIA TERHADAP ABORTUS PADA IBUHAMIL DI RSUD H. ABDUL MANAP KOTA JAMBI - Olivia Tri Monica; Yolanda Seftiana Rizki; Nisa Kartika Ningsih; Dwi Haryanti (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2023)
Background: Abortion is the termination of a pregnancy when the gestational age is less than 22 weeks or the fruit of a pregnancy that cannot live outside the womb with a fetus weighing less than 500 grams. Abortion is a fetus that is released weighing less than 500 grams or has a gestational age of less than 20 weeks at the time of discharge from the uterus so that it has no hope of survival (Riski Nur Marcelina, 2021). Method: This study used a retrospective approach. The population in this study were all pregnant women who had a gestational age of less than 20 weeks at H. Abdul Manap Hospital, Jambi City in 2021-2022, totaling 229 people. Out of 229 people, there were 70 samples of pregnant women using the slovin formula taken randomly. by using the draw lottery system. The sampling technique uses simple random sampling Result: The results of the research that has been done show that the results of data analysis using the Chi Square statistical test show that factors related to abortion are maternal age p-value = 0.039 (≤0.05), Pregnancy Distance p-value = 0.023 (≤0.050), and Anemia p-value = 0.044 (≤ 0.05) Conclusion : The conclusion of this study is that there is a relationship between age, pregnancy spacing and anemia with abortion in pregnant women at the H.Abdul Manap Hospital, Jambi City in 2023. It is suggested that it can be a valuable experience and increase insight and knowledge, especially related to abortion.